ANALISIS SOSIOEKOLOGIS MASYARAKAT PETAMBAK DALAM KONTEKS PERUBAHAN IKLIM DI KECAMATAN BALIKPAPAN TIMUR: Socioecological Analysis of Pond Farmers in the Context of Climate Change in East Balikpapan District of Balikpapan City - Cynthia Narulita; Bambang Indratno Gunawan; Said Abdusysyahid (Jurnal Pembangunan Perikanan dan Agribisnis, 2017)
The research is aimed at determining adaptation strategies created by pond farmers, farmers’ perception and the welfare level of farmer families impacted by climate change in East Balikpapan District. The chosen sampling technique was purposive sampling to collect 40 respondents those who are developing pond aquaculture. The research was carried out from March 2016 to January 2017. Data analysis were used qualitative descriptive analysis, Rank Spearman’s correlation analysis and the pond farmers’ terms of trade index. The results showed that farmers’ adaptation strategies to cope with climate change are to increase and decrease water management activities and calcification, to temporarily postpone pond operation, to change the harvest time, to create or to elevate dyke for flood protection and to plant mangrove in the pond and surrounding areas. The correlations between farmers’ perception (X) and perception of climate change (Y) were inversed, weak and not significant. The increased terms of trade during the period of 2015 and 2016 were calculated 1,24 and 1,68 respectively.